Challenges in Implementing Sharia-Based Education: Balancing Regional Autonomy and Children’s Rights in Aceh - Mukhlis Mukhlis; Muhammad Iqbal; Maya Safitri; Hasniyati Hasniyati (UIN Sunan Gunung Djati, 2025)
This study analyzes the implementation of Sharia-based education in Aceh through the perspective of regional autonomy and children's rights. This multidisciplinary study reveals the tension between Aceh's education policies (Law No. 11/2006 and Qanun Education) with the obligation of children's rights (children's rights convention Articles 28-29 and Child Protection Law No. 35/2014). Findings show that some schools do not meet inclusive standards, religious materials are less multicultural, and only some teachers are trained in inclusive pedagogy with infrastructure gaps. The impact on children's rights is significant: female dropout rates are higher due to child marriage and only some schools are disability friendly. Policy analysis revealed that Qanun has not fully adopted the principle of inclusivity, while policies in the district still ignore marginalized groups. The research introduced the